Analisis kinerja keuangan dengan metode Economic Value Added (EVA) pada PT. Indofood Sukses Makmur Tbk Tahun 2020-2023 - Larage, Godeliva; Tirayoh, Victorina Z.; Maradesa, Djeini (Manajemen Bisnis dan Keuangan Korporat, 2025)
Business in Indonesia is growing rapidly, demanding companies to create sustainable economic value. In the context of the food and beverage industry, the EVA method is a critical analysis tool to evaluate a company’s performance comprehensively. This study aims to analyze the financial performance of PT Indofood Sukses Makmur Tbk in 2020-2023 using the Economic Value Added (EVA) method. This type of research is quantitative research using a descriptive approach. The types of data are qualitative and quantitative, with secondary data sources. The data collection method used is the documentation method. The data analysis method is by using Economic Value Added (EVA). The results of this study show that PT Indofood Sukses Makmur Tbk experienced challenges in creating value for shareholders during 2020-2023, with EVA remaining negative despite fluctuations in NOPAT and Capital Charge. Although NOPAT increased in 2023, EVA still showed negative numbers, reflecting the need for better management of capital costs. Overall, companies need to focus on improving operational profitability to create sustainable, long-term value.